Linking the Industrial Revolutions and Environmental Impacts: A Review of Global Trends, Strategies, and Future Recommendations - Hadiqa Ahmad; Muhammad Yaqub; Seung Hwan Lee (Pakistan Journal of Analytical & Environmental Chemistry)
The Industrial Revolutions (IRs) have dramatically reshaped the industrial landscape by introducing automated production and technological advancements. While these revolutions have driven substantial socioeconomic changes in society, organizations, and government relationships, they have also had significant environmental impacts. These include air, water, and soil pollution, habitat loss, deforestation, resource depletion, food insecurity, and water scarcity. Despite these challenges, IRs hold potential for mitigating environmental damage, such as reducing carbon emissions, soil and water contamination, and resource consumption. Moreover, developing sensors and networks can offer critical insights into environmental changes, aiding the implementation of adaptation and mitigation strategies. This comprehensive review provides a state-of-the-art evaluation of IRs and their environmental interactions, proposing strategies for future environmental policies. It is a valuable resource for future studies and proposals on the digital transformation associated with IRs and their environmental impacts.